2004
DOI: 10.1002/jcla.20013
|View full text |Cite
|
Sign up to set email alerts
|

Reference distributions for α2‐macroglobulin: A comparison of a large cohort to the world's literature

Abstract: The lack of satisfactory methods for quantifying serum levels and a credible reference material has limited bedside use of serum alpha(2)-macroglobulin (alpha2M) measurements. Great strides have been made in the last few years. The remaining barrier to more relevant and cost effective use of serum protein data for diagnosis and prognosis is the availability of reliable reference intervals from birth to old age for both males and females. A total of 40 publications reporting reference intervals have been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
2
11
0
1
Order By: Relevance
“…The conclusion is that a 2 M levels are unaffected. As measured by CRP in the world's literature where small cohorts can often have their health status verified (65,66), inflammation shows a remarkable spread of concentration with less than a quarter of the papers being consistent with our data (37). Reference ranges for this protein over a life-time and between the sexes has been described in a large cohort for the first time.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The conclusion is that a 2 M levels are unaffected. As measured by CRP in the world's literature where small cohorts can often have their health status verified (65,66), inflammation shows a remarkable spread of concentration with less than a quarter of the papers being consistent with our data (37). Reference ranges for this protein over a life-time and between the sexes has been described in a large cohort for the first time.…”
Section: Resultssupporting
confidence: 88%
“…Since the half-life of these drugs is short, only carefully designed studies could take their usage into account. As shown in our companion paper (37) and in previous papers (32)(33)(34)(35), our data compares favorably with only some of the previous small studies that employed guidelines defining health status (65,66) but did not adjust for age or sex.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to findings in serum, similar hK4 complexes were not observed in seminal plasma (data not shown), although ␣ 2 -macroglobulin is known to be present in this fluid (50 ). One explanation may be that the amount of ␣ 2 -macroglobulin varies widely, ranging from 1 to 1000 g/L in seminal plasma (51 ), and that this is only a fraction of the protein found in serum, where concentrations range from 1.5 to 5 g/L in healthy individuals (52 ). Complexing of hK4 with serum serine proteinase inhibitors, leading to nonimmunoreactive complexes, may be another explanation for the lack of serum immunoreactivity of hK4.…”
Section: Discussionmentioning
confidence: 95%
“…A study investigating a-2-macroglobulin levels in a large group (n = 40,420) reported a steady increase after the age of 45, with females having constantly higher mean a-2-macroglobulin levels [27]. A review of the available literature came to very similar findings, reporting an increase in a-2-macroglobulin levels after the age of 40-50, with constantly higher mean values for females [28].…”
Section: Rationale Of Plasmapheresis For Ishlmentioning
confidence: 52%